Response inhibition in the parametric Go/No-Go task in psychopathic offenders. (April 2017) - Weidacker, Kathrin; Snowden, Robert J.; Boy, Frederic; Johnston, Stephen J.
Abstract: Previous research on response inhibition in psychopaths has failed to find consistent evidence for aberrant inhibitory ability, despite strong expectations to the contrary. However, previous examinations have utilised inhibition paradigms that suffer from critical shortcomings, such as a lack of ecological validity and overly simplistic response criteria. To assess inhibition under conditions close to the demands of everyday settings, the current study employs a parametric Go/No-go task in male offenders ( n 77). Additionally, rather than treating psychopathy as a categorical descriptor, a dimensional approach is taken to assess the relationship between individual psychopathic traits and response inhibition performance. Results indicate significant relationships between response inhibition and individual facets of psychopathy as measured by the Psychopathy Checklist: Screening Version. A positive relationship was found between inhibitory ability and interpersonal aspects of psychopathy, reflecting an enhancement of inhibitory functioning for those scoring high on this facet. In addition, a negative association was found between psychopathic lifestyle characteristics and response inhibition. Whereas the negative association mirrors the conceptualisation of the lifestyle facet, the positive association between interpersonal psychopathic aspects and response inhibition might reflect a propensity for adaptive behaviour that enables psychopaths to adequately manipulate their victims and mask their true nature. Highlights: Response inhibition performance depends on the expression of psychopathic traits. High scores on the interpersonal facet relate to improved response inhibition. High scores on the lifestyle facet predict worse response inhibition.